Role of stem cells in arteriovenous access: perspective from Lower Middle Income Countries - Nadeem Ahmed Siddiqui; Aden Javed; Ahsan Raza Raja (Journal of the Pakistan Medical Association, 2023)
Adequately created well functional haemodialysis access is an important part for the physical and mental wellbeing of renal failure patients. Every effort should be made to enhance the patency of these accesses. Recently, stem cell treatment modalities have opened new avenues in the better patency of arteriovenous fistula. Use of mesenchymal stromal cells (MSC) to prevent venous neointimal hyperplasia have been studied with good success rates. Adopting such costly treatment modalities in low middle income class country like Pakistan is associated with significant challenges. This short report discusses the current role of stem cells in arteriovenous access and how this exciting modality can be utilized in our country. Key Words: Dialysis access, arteriovenous fistula, Stem cell, Mesenchymal stromal cell.